2009
DOI: 10.1111/j.1750-3841.2009.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Listeria Monocytogenes by Lauric Arginate on Frankfurters Formulated with or without Lactate/Diacetate

Abstract: Listeria monocytogenes (Lm) is a food safety concern that can be associated with ready-to-eat (RTE) meat and poultry products because of its persistence in the processing environment. Listeriosis has a fatality rate of 28% in immuno-compromised individuals. RTE meats receive a lethal heat treatment but may become contaminated by Lm after this treatment. Federal regulators and manufacturers of RTE meats are working to find additional ways to control postprocess contamination by Lm in RTE meats. This research wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…The strongest deviations from the control resulted with the addition of sodium lactate (0.61 points). The slight influence of organic acids and lauric arginate on the sensory characteristics of foods has been also been reported in previous studies (Barmpalia et al, 2004;Martin et al, 2009;Stekelenburg, 2003;Stekelenburg & Kant-Muermans, 2001;Taormina & Dorsa, 2009b). The addition of sodium diacetate (1 Â 10 3 mg/g) and potassium lactate (30 Â 10 3 mg/g) to Frankfurter type sausages result in a slightly hot and sour taste.…”
Section: Sensory Evaluationmentioning
confidence: 53%
See 3 more Smart Citations
“…The strongest deviations from the control resulted with the addition of sodium lactate (0.61 points). The slight influence of organic acids and lauric arginate on the sensory characteristics of foods has been also been reported in previous studies (Barmpalia et al, 2004;Martin et al, 2009;Stekelenburg, 2003;Stekelenburg & Kant-Muermans, 2001;Taormina & Dorsa, 2009b). The addition of sodium diacetate (1 Â 10 3 mg/g) and potassium lactate (30 Â 10 3 mg/g) to Frankfurter type sausages result in a slightly hot and sour taste.…”
Section: Sensory Evaluationmentioning
confidence: 53%
“…4). This is in contrast to literature (Martin et al, 2009;Porto-Fett et al, 2010;Stopforth, Visser, Zumbrink, van Dijk, & Bontenbal, 2010). It should be noted though that in the references, lauric arginate was used as a surface treatment and not as part of a matrix formulation approach.…”
Section: Samplementioning
confidence: 74%
See 2 more Smart Citations
“…Authors suggested that LAE and organic acids acted synergistically with LAE causing an initial reduction in the level of L. monocytogenes and organic acids subsequently suppressing a re-growth. Similarly, use of combinations of 1.8/0.13 or 2.1/0.15 g/100g potassium lactate/sodium diacetate with 22 ppm LAE caused a two log reduction in L. monocytogenes contaminated Frankfurters (Martin et al, 2009).…”
Section: Growth Over Time Behavior In the Presence Of Binary Antimicrmentioning
confidence: 98%